Pengaruh Likuiditas, Struktur Modal, dan Profitabilitas terhadap Nilai Perusahaan pada Industri Sub Sektor Farmasi yang Terdaftar Di Bursa Efek Indonesia Tahun 2015 – 2019 - Ira Febrianti; Mufidah Mufidah (Jurnal Ilmiah Universitas Batanghari Jambi, 2021)
This research aims to analize the effect of liquidity, equity structure and profitability on firm value in pharmacy manufacturing companies listed on The Jakarta Stock Exchange. Research Methodology use the data panel regression analysis method with the model used is fixed effect. The result of the F test show that liquidity, equity structure and profitability together effect the firm value. Meanwhile, in the t test, only profitability has an influence on firm value.